Satisfied With Less? Mismatch Between Subjective and Objective Position of Immigrants and Native-Born Men and Women in the Labor Market - Amit, Karin; Chachashvili-Bolotin, Svetlana (Frontiers in Sociology, 2018)
The current study introduces a new mismatch concept in labor studies, the mismatch between subjective work perceptions and actual labor market position, and examines it from the perspectives of gender, ethnic and migration. This mismatch, positive or negative, was examined among men and women from different ethnic groups in Israel, both immigrants and native-born. The analyses were conducted on 9,923 employees using the Israeli CBS Social Surveys (2013-2015). The results reveal that the gender effect is more prominent than the ethnicity and migration effect. In general, women were more satisfied with their actual position in the labor market (positive subjective mismatch) than men, and men were less satisfied with their actual position in the labor market (negative subjective mismatch) than women. A positive subjective mismatch was also found among men from disadvantaged ethnic and immigrant groups. The multivariate analyses revealed that after controlling for socio-economic variables, ethnic differences declined among both men and women. Possible explanations are discussed, primarily based on the notion of relative well-being in respect to workers' expectations.